Forecasting Revenues Using the Economic Value Added to Explain Their Real Value (Applied study) - Shatha Abdul Hussein Jaber; Shaima Salah Hassan (Journal of Madenat Alelem University College, 2021)
This research seeks to test the two models in the evaluation of ordinary shares, which are (the equivalent cash model, and the economic value added model) to explain the true value of one share, and a comparison between the two models to see how accurate the second model of economic value added is in the interpretation of returns on stocks and its use instead of the equivalent cash model, and the use of returns as a measure of the value model The economic sample added, the research sample included (9) banks that were listed on the Iraq Stock Exchange and where all the terms of the research were available for the period (2014-2018). The research reached a set of conclusions, the most important of which is the use of the economic value added model as the best in determining the real value of the ordinary shares listed in the Iraq Stock Exchange and because it gave a high explanatory ability, due to the difference in the stock price.